Pengembangan Training Procedure Manual (Tpm) pada Approved Training Organization (Ato) untuk Efektivitas Pengelolaan Pelaksanaan Pelatihan - Machmiyana, Ichyu; Jatmoko, Djoko; Tri Saputra, Surya; Rahajeng Larasati, Emilia (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
The Training Procedure Manual (TPM) is a document used as a guideline for the Approved Training Organization (ATO) in organizing education and training. Indonesian Aviation Polytechnic (PPI) Curug as an Approved Training Organization has several approvals from the Director General of Civil Aviation. Each approval has a TPM in accordance with their respective fields. In 1 (one) Approved Training Organization (ATO) one should have 1 (one) TPM document, but currently, PPI Curug has several TPMs and each TPM document is not aligned with the current PPI Curug organization. The purpose of this research is to harmonize all areas of approval that have been owned by PPI Curug through the design of the Institutional Training Procedure Manual (TPM). The method used is Research and Development (RnD). Research and Development (RnD) are used to produce certain products and test the effectiveness of these products. The results of this study are the Institutional Training Procedure Manual (TPM) draft as the main document of the TPM for each field which is aligned with the PPI Curug organization